The Impact of Contingent Convertible Bonds on Bank Profitability: Evidence from the EU15 Banking Sector - Kinlocke, G (2017)
Following the financial crisis, regulators increased the amount of required quality and quantity of capital in banks. Due to the costly nature of capital, banks created a new financial instrument that would satisfy incoming capital regulation and optimise funding costs. This instrument is the contingent convertible bond (CoCo). CoCos are hybrid capital securities that absorb losses when the capital of the issuing bank falls below a particular level (Avdjiev, 2013). A number of studies have examined the various advantages CoCos provide. However, few have reviewed the impact of CoCos on bank profitability. This paper aims to investigate the research question - To what extent does CoCo bond issuance affect bank profitability in the EU15? The fixed effects (FE) estimation technique was used to run bank performance regressions on the top 100 EU15 banks ranked by size. The results show that CoCo bonds have a statistically significant and positive effect on bank profitability. The findings from this paper have important implications for banks aiming to optimise business performance in anticipation of Basel III. The findings also provide further support for regulators’ active encouragement of CoCos to absorb losses in times of distress.